PSYCHOPATH IN GONE GIRL: A STUDY OF GENRE - Aditira, Evia Nurdiarti (English Teaching Journal, 2015)
The researcher investigated the relationship between psychopath genre movie and society. It aims to describe and analyze the development of formula in psychopathic genre and to find the reason why this genre entertains the audience. This research deals with analyzing genre in psychopathic movies through Gone Girl. In this research, the researcher uses qualitative research method. There are 20 movies used in this analysis. Those movies are taken from several production houses during the year 1971 - 2014.Â All of this movies tell about female psychopath. The researcher uses concept of formula based on Caweltiâs theory. There are five formulas in psychopath genre movie and it has developed over the time. The changing of psychopath genreâs formulas is based on desire of society. Environment become a major factor of someone to be psychopath. Many criminality and pressure happen in our society affect the increasing number of psychopath. It is the reason why this genre still exist because it reflects societyâs life.